External differentiated integration between Turkey and the European Union: the customs union and its revision - ÖZER, YONCA (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
The European Union (EU)-Turkey customs union (CU) has led to a significant level of integration between a non-member country and the EU and therefore represents an example of external differentiated integration. Turkey's relations with the EU, until recently, have been largely motivated by its membership objective. However, Turkey's membership prospects have recently been diminishing, due both to mutual estrangement because of Turkey's ever-deteriorating performance on EU-mandated reforms and the current difficulties challenging European integration. Under these circumstances, concerns regarding structural problems and conjunctural challenges have forced both parties to revise the CU. This study aims to explain how the parties should revise it to tackle the challenges posed by current economic relations. It argues that building broader and deeper economic integration with a certain degree of collective policy-making capacity will be crucial for furthering relations, which may thereby contribute to Turkey's accession process in a longer term.
Keywords: Turkey-EU relations; economic integration; customs union; differentiated integration